托法替布在慢性斑块型银屑病中的获益风险特征. (2nd January 2019) - Strober, B.E.; Gottlieb, A.B.; van de Kerkhof, P.C.M.; Puig, L.; Bachelez, H.; Chouela, E.; Imafuku, S.; Thaçi, D.; Tan, H.; Valdez, H.; Gupta, P.; Kaur, M.; et al.
Abstract : Linked Article: Strober et al. Br J Dermatol 2019;180 :67–75